2003
DOI: 10.1124/mol.64.2.373
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and Propofol Inhibit Voltage-Gated Sodium Channels in Isolated Rat Neurohypophysial Nerve Terminals

Abstract: Mounting electrophysiological evidence indicates that certain general anesthetics, volatile anesthetics in particular, depress excitatory synaptic transmission by presynaptic mechanisms. We studied the effects of representative general anesthetics on voltage-gated Na ϩ currents (I Na ) in nerve terminals isolated from rat neurohypophysis using patch-clamp electrophysiological analysis. Both isoflurane and propofol inhibited I Na in a dose-dependent and reversible manner. At holding potentials of Ϫ70 or Ϫ90 mV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
100
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 45 publications
4
100
3
2
Order By: Relevance
“…12,13 Inhaled anesthetics are also known to have Na + channel blocking activities, not only on the central nervous system, but also on the peripheral nervous system. [14][15][16] Accordingly, it is possible that inhaled anesthetics may exert their cutaneous analgesic effect through similar Na + channel blocking activities on the cutaneous nervous system, although more studies are needed to confirm this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Inhaled anesthetics are also known to have Na + channel blocking activities, not only on the central nervous system, but also on the peripheral nervous system. [14][15][16] Accordingly, it is possible that inhaled anesthetics may exert their cutaneous analgesic effect through similar Na + channel blocking activities on the cutaneous nervous system, although more studies are needed to confirm this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stadnicka et al (1999) showed that isoflurane, as well as halothane, suppressed heart sodium channels expressed in HEK293 cells by acceleration of the transition from the open to the inactivated state and stabilization of the inactivated states (Stadnicka et al, 1999). Moreover, isoflurane inhibited voltage-gated Na ϩ currents in a concentration-and voltage-dependent manner in isolated rat neurohypophysial nerve terminals, and the inhibition by isoflurane had no significant effects on V 1/2 of the activation curve, but the V 1/2 of the inactivation curve was consistently shifted in a negative direction (Ouyang et al, 2003).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It has been thought that axonal conduction, and by inference voltage-gated Na ϩ channels, are not affected by reasonable concentrations of anesthetics (Franks and Lieb, 1994). However, more recent studies show that anesthetics at clinically relevant concentrations can suppress Na ϩ channel function in synaptosomes (Ratnakumari and Hemmings, 1998), neurohypophysial nerve terminals (Ouyang et al, 2003), and in cells transfected with a rat neuronal sodium channel, Na v 1.2 channel (Rehberg et al, 1996). These studies raise the possibility that Na ϩ channel inhibition can contribute to anesthesia.…”
mentioning
confidence: 89%
“…In hippocampal neurons, this tonic, "extrasynaptic" GABA A component is more sensitive to anesthetics than actions on phasic currents in the same neurons (Hemmings, Jr. et al, 2005) and seemingly plays a substantial role in suppressing neuronal excitability (Bieda & MacIver, 2004). In addition, ion channels and in particular voltage-gated sodium channels are reported to be inhibited by low micromolar concentrations of propofol (Frenkel & Urban, 1991;Ouyang et al, 2003;Jones et al, 2007). Given the diversity in composition and expression of native GABA A receptors as well as potential ion channel targets, accurate predictions of general anesthetic actions within any specific brain region is problematic.…”
Section: Introductionmentioning
confidence: 99%